Evolution of European Resuscitation and End-of-Life Practices from 2015 to 2019: A Survey-Based Comparative Evaluation - Mentzelopoulos, Spyros D; Couper, Keith; Raffay, Violetta; Djakow, Jana; Bossaert, Leo (Journal of clinical medicine, 2022)
BACKGROUND: In concordance with the results of large, observational studies, a 2015 European survey suggested variation in resuscitation/end-of-life practices and emergency care organization across 31 countries. The current survey-based study aimed to comparatively assess the evolution of practices from 2015 to 2019, especially in countries with "low" (i.e., average or lower) 2015 questionnaire domain scores. METHODS: The 2015 questionnaire with additional consensus-based questions was used. The 2019 questionnaire covered practices/decisions related to end-of-life care (domain A); determinants of access to resuscitation/post-resuscitation care (domain B); diagnosis of death/organ donation (domain C); and emergency care organization (domain D). Responses from 25 countries were analyzed. Positive or negative responses were graded by 1 or 0, respectively. Domain scores were calculated by summation of practice-specific response grades. RESULTS: Domain A and B scores for 2015 and 2019 were similar. Domain C score decreased by 1 point [95% confidence interval (CI): 1-3; p = 0.02]. Domain D score increased by 2.6 points (95% CI: 0.2-5.0; p = 0.035); this improvement was driven by countries with "low" 2015 domain D scores. In countries with "low" 2015 domain A scores, domain A score increased by 5.5 points (95% CI: 0.4-10.6; p = 0.047). CONCLUSIONS: In 2019, improvements in emergency care organization and an increasing frequency of end-of-life practices were observed primarily in countries with previously "low" scores in the corresponding domains of the 2015 questionnaire.